Focussing on teacher talk in motivating students in the English Language classroom at Universiti Teknologi MARA (UiTM) / Alauyah Johari - Johari, Alauyah (UiTM cawangan Kedah, 2003)
This paper looks at the various aspects of teacher talk in the English Language classroom. This is based on classroom observations and unpublished classroom research done over a period of ten years. Teacher talk is dealt in three aspects: amount, quality and timing of teacher talk. A more detailed discussion is done on the timing of the teacher talk. Finally suggestions are made to help teachers use teacher use his/her talk to benefit everybody in class.